1987
DOI: 10.1128/aac.31.7.1111
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antibacterial activities of T-2588, a new oral cephalosporin, compared with those of other oral beta-lactam antibiotics

Abstract: T-2588, the pivaloyloxymethyl ester of T-2525, [6R, 7R]-7-[(z)-2-(2-aminothiazol-4-yl)-2-methoxyiminoacetoamido] -3- [(5-methyl-2H-tetrazol-2-yl)methyl]-3-cephem-4-carboxylic acid, is a new oral cephalosporin. T-2525 had a widely expanded antibacterial spectrum against gram-negative and gram-positive bacteria. T-2525 was more active in vitro than cefaclor, cephalexin, and amoxicillin against members of the family Enterobacteriaceae and Branhamella catarrhalis. Moreover, it exhibited superior in vitro activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…T-2525 (cefterame) is the biologically active product of the orally administered prodrug (T-2588). T-2525 is active against gram-negative bacteria and Streptococculs pneumoniae, but is less active than cefaclor against staphylococci (2,11,13). R-3746 is the biologically active product of CS-807.…”
mentioning
confidence: 99%
“…T-2525 (cefterame) is the biologically active product of the orally administered prodrug (T-2588). T-2525 is active against gram-negative bacteria and Streptococculs pneumoniae, but is less active than cefaclor against staphylococci (2,11,13). R-3746 is the biologically active product of CS-807.…”
mentioning
confidence: 99%
“…Thus, in this study, only 7 of 50 members of the Enterobacteriaceae were resistant to cefaclor but susceptible to cephalexin. A number of other investigators have also observed this difference in ,-lactamase stability between cefaclor and cephalexin (1,2,8,11,16,17,20,26). However, the difference is most apparent when a cephalosporin rather than a penicillin is used as the standard for comparison.…”
Section: Methodsmentioning
confidence: 83%
“…Rather, it appeared to result from the high affinity of the drug for target enzymes. There has recently been intense activity in the development of new orally absorbable cephalosporins. Some of these compounds are directly absorbable in their active forms (2,6,7,10,11,13,16,28,30), while others are esters which must be enzymatically cleaved to their active forms after absoi-ption (3,5,9,17,18,20,27,29). Many of these newer compounds possess expanded antimicrobial spectra compared with spectra of older oral cephalosporins, which is thought to be due in large part to a diminished susceptibility to hydrolysis by 1-lactamases (1-6, 8, 9, 15-17, 19-21, 26, 27, 29).…”
mentioning
confidence: 99%
“…Cefaclor is active against gram-positive and some gram-negative bacteria but is hydrolyzed by various f-lactamases (13). Cefixime and cefteram (T-2525) (2,12,14) have good activity against gram-negative bacteria and streptococci and are not hydrolyzed readily by various P-lactamases, but these compounds have relatively low activities against staphylococci (2,6,12,14).…”
mentioning
confidence: 99%
“…BMY-28232 and BMY-28271 (the acetoxyethyl ester of BMY-28232) were synthesized at the Tokyo Research Center of Bristol Myers Research Institute, Ltd., Tokyo, Japan.-The other antimicrobial agents used in this study were obtained from the indicated sources: cefixime, Fujisawa Pharmaceutical Co., Ltd., Osaka, Japan; cefteram (T-2525, Ro 19-5247) and cefteram pivoxil (T-2588) (2,12,14), Toyama Chemical Co., Ltd., Tokyo, Japan; cefaclor, Shionogi Pharmaceutical Co., Ltd., Osaka, Japan; benzylpenicillin, Meiji Seika Kaisha, Ltd., Tokyo, Japan; cephaloridine, Nihon Glaxo Co., Ltd., Tokyo, Japan; and methicillin, Banyu Pharmaceutical Co., Ltd., Tokyo, Japan. Organisms. The bacterial strains used in this study were recent clinical isolates from various hospitals in Japan.…”
mentioning
confidence: 99%